Wireless data communication for autonomous farming & precision agriculture applications: harnessing ISM band radio for real-time data connectivity & monitoring to enhance data analysis and logistic operations - Shende, Ketan (Kansas State University, 2024)
Recent advancements in autonomous farming and precision agriculture have significantly enhanced machinery and systems, enabling large-scale automation and upgrades for growers. Efficiently managing real-time information is vital for these dynamic systems due to their significant variabilities. The adoption of wireless data communication facilitates instantaneous information handling, ensuring seamless data transfer. Amongst the demand for efficient wireless data communication solutions continues to rise, the utilization of license-free spectrum band radios, particularly Industrial, Scientific, and Medical (ISM) band, has expanded. This research aims to leverage these radios to establish a data communication platform for transferring information independently or when integrated with an autonomous liquid application system. Additionally, these radios communicate RTK correction signals to improve image triggering and geotagging accuracy in UAV remote sensing. To demonstrate an end-to-end wireless data communication link, a platform referred as Pico Radio Interface Microcontroller Electronics (PRIME) board, was designed using a PICO 900 radio, a Teensy 4.1 microcontroller and power electronics component. The radio with a link rate of 276 kbps, 40 miles (60 km) LOS, and power of 1 Watt was utilized to build a network of 4 remotes, 2 repeaters, and a master. The remotes were configured to continuously transfer simulated information to the master at the central hub with repeaters which are in secondary configuration are used to expand the scope of the network. The data communication system was deployed in outdoor environment consisting of undulating terrain and dense crop canopy and was tested for its transmission efficacy for 15-, 25-, and 30-minutes experiment. A packet delivery ratio of greater than 0.98 was observed meaning a successful packet transmission of more than 98% for per second data transfer and close to 100 % for per 30 second data transfer in both the field conditions and for all the experimental runs. Also, a power consumption of less than 0.42 watts was attained proving the power efficiency of the PRIME boards. Further, to gauge the data communication ability of the license free spectrum band radio operating in 2.4 GHz frequency, a combination of 2X2 Multiple Input Multiple Output (MIMO) radio modules is configured for setting up a wireless data link between an autonomous rover platform and a central hub for real-time data accumulation. The radio with extensive speed of 25 Mbps and low power consumption is integrated with autonomous platform using ROS2 middleware. The data packets consist of system-level details, including location information, signal status, and operational metrics like target detection, nozzle pressure, and tank level. These are gathered from three onboarded subsystems: navigation, computer vision, and site-specific liquid application. Two out of three configuration were able to achieve a packet delivery ratio of more than 98% and collective loss of less than 2 % for a timed experiments of 5 minutes each in two different environments. Data packet latency was also calculated between the transmission where a range between 0.1 to 0.4 seconds was observed for both the environments. This proved the ability of the MIMO radios operating in license free spectrum to be deployed in autonomous farming application and collect information from mobile platforms. A wireless data communication radio setup is used to improve the image triggering and image geotagging accuracy for a UAV based remote sensing application. A Real-Time Kinematics (RTK)-enabled GNSS solution was designed to achieve a cm-level accuracy for a UAV based imagery data collection for consumer-grade RGB cameras as well as Thermal Infrared Cameras (TIR). This consisted of a base station setup that generated RTK correction signals which are serially sent to a transmitting radio operating in 900 MHz license free spectrum band. The receiving radio which is onboard with the GNSS solution collects the RTK-signals and feeds them to the GNSS module which rectifies the location information. For the flights conducted to test the image triggering mechanism, the radio was able to communicate 80 % of RTK signals for both the 20 m and 30 m flight. The RTK-enabled data points were in the range of 0.36 to 3.48 m for the 20 m flight whereas 0.37 to 3.6 m for the 30 m flight. Whereas to assess the image geotagging accuracy, the radio was able to communicate 86% of the time during 50 m flights and 93% of the time during 80 m. RTK-enabled flight data points were in the range of 0.7 meters to less than 3 m for 50 meters flight and 0.6 meters to 2.75 meters for the 80 m flight. This proved the ability of the radios to communicate information in real-time for a dynamic UAV remote sensing application improving the image triggering & geotagging accuracy. In conclusion, this research underlined the ability of radio communication operating in license free spectrum band to effectively communicate information for end-to-end data transfer and improving the ability of image triggering and geotagging for remote sensing applications by communicating RTK correction signals.
Keywords: Wireless data communication; Real-time data transfer; License-free radio communication; Autonomous farming; Precision agriculture